AKTUALISASI PERILAKU KEBERAGAMAAN REMAJA (Studi Deskriptif Analitik di Madrasah Aliyah Diniyyah Putri Lampung) - Umar, Jusnimar (Analisis: Jurnal Studi Keislaman, 2014)
ACTUALIZATION OF RELIGIOUS BEHAVIOR AMONG THE YOUTH (An Analytical,  Descriptive  Study in Madrasah Aliyah Diniyyah  Putri  Lampung):  This article  is the result  of research activities conducted at Madrasah Aliyah Diniyah Putri Lampung. The goal is to formulate a better religious behavior actualization activity patterns specifically targeted to the young women. Departing from the assumption that young women are vulnerable to a variety of adverse effects of the mass media, religious education at boarding school, therefore, is carried out more intensively than with the ongoing implementation of religious education in public schools. This study found that the actualization of religious behavior among students has been quite successful and can lead to significant changes to the student’s behavior for the better. These changes in behavior can be measured from a number of specific indicators, among others: (a) having a good faith, (b) performing the true worship, (c) well-mannered  (d). Sociable (relationships among  fellow  students,   teachers  and  madrasah personnel  are close and harmony),  (e) politics  (respectful  to other’s  opinion), (f) thrifty  (economical and mutual assistance  to each other), (g) dignity (maintaining the dignity and nature as women), (h) loving peace (create  tranquility  and peace within  their own milliues), and (i) having the freedom of thought and speech.